Tissue Specific Esterase Isozyme Banding Pattern in Nile Tilapia (Oreochromis niloticus) (University Journal of Zoology, Rajshahi University, 2009)
The electrophoretic banding pattern of esterase isozymes were examined in eighteen different tissues of Nile tilapia after staining with Î± and Î² naphthyl acetate as substrate. The tissues were anterior-, mid-, tailmuscle (ventral and tip region), buccal muscle, stomach, fore-, mid-, hind-gut, liver, gill, heart, kidney, eye (lens), eye (iris), fore-, mid- and hind- brain. Altogether five bands named as Est-11.4, Est-21.1, Est-31, Est-40.62 and Est-50.25 were observed different relative mobility. Est-1 and Est-5 denote the fastest and slowest band. Est-3 was present in all the tissues. All five bands were expressed in liver and stomach. Some of the esterase bands showed tissue and substrate specificity, where Est-1 was in fore-, mid- and hind- brain, Est-2 in hind gut, Est-5 in stomach, gill and heart was stained only with Î± naphthyl acetate. None of the band was expressed with Î² naphthyl acetate only. Key words: esterase, isozyme, Oreochromis, tissue Â  Doi:10.3329/ujzru.v27i0.1942 Univ. j. zool. Rajshahi Univ. Vol. 27, 2008 pp. 01-05